2019
DOI: 10.1111/ijd.14509
|View full text |Cite
|
Sign up to set email alerts
|

Are new variants of psoriasis therapy (IL‐17 inhibitors) safe?

Abstract: Psoriasis is a chronic, recurrent, inflammatory, and proliferative skin disease. Its etiology has not yet been fully assessed, but undoubtedly it is a multifaceted disease. The key role in its pathomechanism is played by genetic, immunologic, and environmental factors and stress. If traditional methods of psoriasis treatment (phototherapy, methotrexate, retinoids, cyclosporine A) fail, we reach for the following biopharmaceuticals – infliximab, etanercept, adalimumab, or ustekinumab. However, genetic engineeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…61,62 Another IL-17 inhibitor under phase III studies for psoriasis that could potentially be used for HS includes ixekizumab. 63,64 A recent open-label cohort study of 10 patients treated with subcutaneous brodalumab (anti-17A, IL-17C and IL-17F) showed promising results. 65 Bimekizumab (a dual IL-17A and IL-17F inhibitor) is currently under phase II multicentre clinical trials for moderate-to-severe HS (NCT03248531).…”
Section: Tumour Necrosis Factor-alphamentioning
confidence: 99%
See 2 more Smart Citations
“…61,62 Another IL-17 inhibitor under phase III studies for psoriasis that could potentially be used for HS includes ixekizumab. 63,64 A recent open-label cohort study of 10 patients treated with subcutaneous brodalumab (anti-17A, IL-17C and IL-17F) showed promising results. 65 Bimekizumab (a dual IL-17A and IL-17F inhibitor) is currently under phase II multicentre clinical trials for moderate-to-severe HS (NCT03248531).…”
Section: Tumour Necrosis Factor-alphamentioning
confidence: 99%
“…Previous studies have demonstrated that HS is associated with a significantly increased risk of co‐occurring and new‐onset inflammatory bowel disease (IBD); 60 secukinumab has been associated with worsening symptoms compared with placebo in clinical trials of Crohn disease, and therefore the onset and/or worsening of IBD needs to be closely monitored in phase III trials 61,62 . Another IL‐17 inhibitor under phase III studies for psoriasis that could potentially be used for HS includes ixekizumab 63,64 . A recent open‐label cohort study of 10 patients treated with subcutaneous brodalumab (anti‐17A, IL‐17C and IL‐17F) showed promising results 65 .…”
Section: Interleukin‐17mentioning
confidence: 99%
See 1 more Smart Citation
“…8 The use of biological IL-17A inhibitors can result in the appearance of some side effects such as infection, nasopharyngitis, upper respiratory tract infections, inflammation on the nasal mucosa, headaches, and candida infections. 9 In recent years, hypertrichosis has been reported in anecdotal cases or series cases. 1,2,10 Rongioletti et al, 2 reported on a patient with erythrodermic psoriasis who was treated with secukinumab.…”
Section: Discussionmentioning
confidence: 99%
“…In the skin, Langerhans cells recognize fungal pathogens, which drive TLR/MYD88 and dectin-1-dependent pathway and subsequently produces IL-6 mediated IL-17-producing cell development [12,37]. Blockages of IL-17 and IL-23 reduce chemokine and antimicrobial expression, and increase the risk of systemic fungal burden [38,39]. Therefore, it is assumed that humans have developed immune reactions against fungal cell components to eliminate infection and as the host immune response, and that IL-17 plays a vital role in the host defense against fungal infection.…”
Section: Pattern Recognition For Il-17 Induction Against Fungimentioning
confidence: 99%